Coplanar waveguide wideband bandpass filter and its application to ultra-wideband pulse generation - Mondal, Priyanka (2013)
A technique to design wideband coplanar waveguide bandpass filters is reported. The filter is realized by etching a slot on the ground plane around a gap on its central conductor and modifying the gap in the form of parallel lines. It is shown that the 3-dB fractional bandwidth of the filter can be varied from 60 to 110% by tuning the size of the slot aperture and the length of the parallel lines. Equivalent circuit and design steps are presented. Implementation area of the filter having passband 3.2–10.5 GHz is 0.90 λg × 0.26 λg, λg being the guided wavelength at 6.85 GHz while 20-dB stopband is at least up to 18 GHz. Insertion loss is less than 2 dB up to 9 GHz. Area of the filter having fractional bandwidth 60% at 3.85 GHz is 0.67 λg × 0.11 λg. Passband loss is within 1.5 and 20 dB stopband is at least up to 12 GHz. The proposed filter structure is very simple to integrate, and the ultra-wideband filter is used to generate an ultra-wideband pulse as defined by the US Federal Communication Commission.